The Gambia : Poverty Reduction Strategy Paper; Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2009)
This Joint Staff Advisory Note discusses the Annual Progress report of The Gambia's Poverty Reduction Strategy Paper. Macroeconomic performance has been strong, exemplified by robust growth and relatively low inflation. However, the current global economic slowdown is likely to adversely affect growth in The Gambia and widen the external current account deficit by slowing down tourism and remittances. In addition to the impact of the global economic slowdown, re-export trade appears to be contracting as the country's regional comparative advantages deteriorate, and foreign direct investment is projected to level off after rising sharply.